SIMULASI RESERVOIR DUA FASA DUA DIMENSI - Hariadi
This study discussed a simulation of two phases reservoir in two dimensions, wieh may be applied as an assesment of the reservoir condition at a time. In this Theses be developed a reservoir simulation with based on the mass conservation, Darcy\"s fluid flow equation, Neumann boundaries condition and the reservoir grid model. In this reservoir simulation conducted several work steps sequently : Physical Model, Mathematical Model, Numerical Model, and the last is the Simulation Model. For this requirement are selected an IMPIS (Implicit Pressure Implicit Saturation) solution method with LSOR (Line Successive Over Relaxation) method is the matrixtridiagonal solution using the Thomas Algorithm formula. To spin round the input datas, simulation process, also oil and water pressure distributions of the model, can be concluded that I. This simulation model can used to predict the real field of reservoir states. 2. To think of various weakness of the model, severals kind of errors of the simulation calculation and many parameters interaction with the reservoir behaviour careless, also using the boundaries condition, that needed some developed methods. For this purpose, the advance modification of methodm is needed for a real conditions of water and oil reservoir in the fields .